Path selection protocols for IEEE 802.11s wlan mesh networks - Bari, S. M. Sadakatil; Anwar, Farhat (IIUM Press, 2011)
Wireless mesh networks (WMN) have been envisioned as an impol1ant solution to the next generation wireless networking. It is a special kind of multihop wireless network that consists of mesh routers and mesh clients [I]. Typically. mesh routers are static and power-enabled and they !(xm a wireless backbone for the WMNs while connected with the wired networks to prm ide multi-hop wireless intemet connectivity to the mesh clients. Mesh clients may be mobile and they can access the network via mesh routers or directly by forming a mesh with each other.